Effects of supplemental chromium sources and levels on performance, lipid peroxidation and proinflammatory markers in heat-stressed quails - Şahin, Nurhan; Akdemir, F.; Tuzcu, M.; Hayirli, A.; Smith, M. O.; Şahin, Kazım (Elsevier, 2010)
This experiment was conducted to evaluate the effects of supplemental Cr source and level on performance, and lipid peroxidation and proinflammatory markers in heat-stressed Japanese quails (Coturnix coturnix japonica). A total of 360 birds (10 days old) were assigned randomly to be reared at either 22 degrees C (thermoneutral, TN) or 34 degrees C (heat stress, HS) for 8 h/day (0900-1700) until the age of 42 days. Birds were supplemented with Cr as chromium chloride (CrCl3) or chromium picolinate (CrPic) at 0.400 and 800 mu g/kg. Each of the 2 x 2 x 3 factorially arranged experimental groups was replicated in 10 cages, each containing 3 birds. Data [performance, serum and liver malondialdehyde (MDA) and serum tumour necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6) and C-reactive protein (CRP)] were analyzed using 3-way ANOVA. The HS condition caused reductions in feed intake (-5.6%), weight gain (-11.9%), cold carcass weight (-13.5%) and carcass efficiency (-1.8%) and an increase in feed efficiency (6.8%) compared to the TN condition (P<0.0001 for all). The HS condition was also associated with 1.9, 1.8, 1.5, 1.5 and 1.7-fold increases in serum MDA, liver MDA and serum TNF-alpha, IL-6 and CRP levels, respectively (P<0.0001 for all). Increase in weight gain (P<0.05), improvement in feed efficiency (P<0.05) and decreases in liver MDA (P<0.03), serum TNF-alpha (P<0.05) and CRP (P<0.006) were greater for quails supplemented with Cr as CrPic than for those supplemented with Cr as CrCl3. Performance variables increased linearly and lipid peroxidation and proinflammatory markers decreased linearly with increasing supplemental Cr level (P<0.01 for all). There were no significant 2-way interactions of the treatments. In conclusion, heat stress caused a decrease in performance variables and increased lipid peroxidation and proinflammatory markers in quails. Increasing supplemental Cr improved performance variables and decreased lipid peroxidation and proinflammatory markers, regardless of its source and environmental temperature. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chromium; Heat stress; Performance; Lipid peroxidation; Proinflammatory markers; Quail